OPTIMIZATION OF ISOLATION, PURIFICATION, AND FREEZE-DRYING FOR BOVINE PLATELET-RICH PLASMA (PRP) TO DEVELOP BIOLOGICAL PRODUCT - Ihsan, Igo Syaiful; Fauziah, Ima; Hendrianto, Eryk; Karsari, Deya; Syah, Alif Firman; Qomar, Nadira Virgin Al (Buletin Veteriner Udayana, 2026)
Platelet-rich plasma (PRP) is an autologous plasma fraction enriched with platelets and growth factors that support tissue repair. In veterinary applications, bovine PRP shows therapeutic potential, but its clinical use is limited by the short stability of fresh preparations. Freeze-drying offers a promising method to improve PRP shelf-life and usability. This study aimed to develop a standardized protocol for bovine PRP isolation, characterization, and freeze-drying. Blood samples (400 mL) were collected from six healthy cows using CPDA-1 anticoagulant. Hematological screening was performed using an automated analyzer. PRP was isolated via a double-spin centrifugation protocol and subsequently lyophilized using a controlled freezing and freeze-drying system. Data were analyzed using descriptive statistics, Shapiro-Wilk normality tests, and Spearman correlations. Hematology profiles showed wide biological variation in WBC, HGB, and HCT, while RBC, MCV, and PLT remained within stable ranges. Double-spin centrifugation effectively increased platelet concentration up to threefold from baseline. Freeze-drying produced stable PRP powder with low residual moisture, suitable for storage at room temperature. Significant positive correlations were found among RBC-HGB-HCT, reflecting normal erythropoietic physiology. The developed protocol successfully standardized bovine PRP isolation and freeze-drying procedures, producing stable and concentrated PRP suitable for extended storage. Freeze-dried bovine PRP has strong potential as a practical biological product for veterinary regenerative applications and cattle health management.Further studies are recommended to evaluate the biological stability and clinical efficacy of freeze-dried bovine PRP in various veterinary therapeutic applications.